A Package for Measuring Emergence, Self-organization, and Complexity Based on Shannon Entropy - Santamaría-Bonfil, Guillermo; Gershenson, Carlos; Fernández, Nelson (Frontiers in Robotics and AI, 2017)
We present a set of Matlab/Octave functions to compute measures of emergence, self-organization, and complexity applied to discrete and continuous data. These measures are based on Shannon’s information and differential entropy. Examples from different datasets and probability distributions are provided to show how to use our proposed code.